Antisense Therapy for a Common Corneal Dystrophy Ameliorates TCF4 Repeat Expansion-Mediated Toxicity - Zarouchlioti, Christina (Am J Hum Genet, 2018)
Fuchs endothelial corneal dystrophy (FECD) is a common disease for which corneal transplantation is the only treatment option in advanced stages, and alternative treatment strategies are urgently required. Expansion (≥50 copies) of a non-coding trinucleotide repeat in TCF4 confers >76-fold risk for FECD in our large cohort of affected individuals. An FECD subject-derived corneal endothelial cell (CEC) model was developed to probe disease mechanism and investigate therapeutic approaches. The CEC model demonstrated that the repeat expansion leads to nuclear RNA foci, with the sequestration of splicing factor proteins (MBNL1 and MBNL2) to the foci and altered mRNA processing. Antisense oligonucleotide (ASO) treatment led to a significant reduction in the incidence of nuclear foci, MBNL1 recruitment to the foci, and downstream aberrant splicing events, suggesting functional rescue. This proof-of-concept study highlights the potential of a targeted ASO therapy to treat the accessible and tractable corneal tissue affected by this repeat expansion-mediated disease.